Warisan Leluhur Sebagai Identitas Bangsa Di Era Globalisasi - Ratnasari Ratnasari; Ferdy Anthonius; Majaputera Karniawan; Meilianti Meilianti (FKIP, Universitas Palangka Raya, 2026)
Ancestral heritage holds a strategic position in shaping the identity of the Indonesian nation. As a country consisting of hundreds of ethnic groups, languages, and traditions, cultural heritage serves as the foundation of values, a symbol of national identity, and a form of social capital for the nation’s sustainability. However, the era of globalization presents new challenges, including the penetration of foreign cultures, rapid modernization, and the weakening transmission of cultural values to younger generations. This study aims to comprehensively examine the role of ancestral heritage in building national identity, analyze the impact of globalization on the sustainability of local traditions, and formulate relevant preservation strategies in contemporary contexts. This research employs a qualitative-descriptive approach with literature study as the primary data collection technique. The literature analyzed includes theories of anthropology, cultural sociology, concepts of national identity, and UNESCO documents related to cultural heritage preservation. The findings indicate that ancestral heritage is not only aesthetic and historical in nature but also contains philosophical and ethical values that can serve as guiding principles for modern society. On the other hand, globalization has ambivalent impacts: it opens spaces for creativity while simultaneously posing a threat to the integrity of local cultural identities. Cultural preservation strategies must involve formal and nonformal education, revitalization of traditional communities, digital innovation, and strong governmental policy support. Through collaborative reinforcement, ancestral heritage can remain alive and relevant, even becoming a national strength in facing global dynamics.